Pomegranate Peel Extract Decreases Plaque Necrosis and Advanced Atherosclerosis Progression in Apoe-/- Mice - Manickam, Vijayprakash; Dhawan, Umesh Kumar; Singh, Damanpreet; Gupta, Mahesh; Subramanian, Manikandan (Frontiers in Pharmacology, 2022)
Atherosclerosis is a chronic lipid-driven inflammatory condition of the arteries and is a leading cause of stroke, myocardial infarction, and other peripheral arterial diseases. Plant products rich in polyphenols such as pomegranate juice and peel extract are known to have beneficial effects in suppressing atherogenesis. However, the mechanism of action and their effect on advanced atherosclerosis progression which results in adverse clinical outcomes are not well understood. Herein, we use a standardized hydroethanol extract of Punica granatum (pomegranate) peel in the Apoe-/- murine model of advanced atherosclerosis. It was observed that the pomegranate peel extract fed mice have decreased plaque necrosis and elevated lesional collagen content which was associated with a favorable metabolic profile including lowering of blood glucose, cholesterol, and triglyceride. The decrease in plaque necrosis was linked with increased lesional macrophage efferocytosis efficiency which was associated with enhanced expression of the efferocytosis receptor Mertk. Using in vitro studies, we show that pomegranate peel extract blocks the shedding of Mertk and preserves macrophage efferocytosis efficiency. These data identify a novel mechanism by which pomegranate peel extract promotes the resolution of inflammation in atherosclerosis.